Recent advances in stability formulae and damage description of breakwater armour layer - Kamali, Babak; Hashim, Roslan (American-Eurasian Network for Scientific Information, Jordan, 2009)
The present paper gives a brief overview of the current state-of-the-art for estimating stability of rubble mound breakwater armour layer, identifying a set of relevant aspects, such as definition of damage, type of armour units, and the sea state. Since all the stability formulae are designed to estimate the appropriate weight of armour units corresponding to a certain damage level, different methods of damage assessment are distinguished, and most well-known stability formulae are discussed with the emphasis on definition of damage.